Building policy coherence related to food systems, soil, and water for coordinated work between governments - Casanova, Alexander Buritica; Yomayuza, Karoll Valentina; Pierce, Deborah (CGIAR System Organization, 2023)
In recent years, countries have suffered various crises – climate or economic. These trends suggest the need for countries to be more resilient. Policy formulation would be central to this. A CGIAR initiative aims to strengthen policymaking in several countries by fostering coherence of national policies and strategies (NPS). In this interview, Dr. Augusto Castro, who leads the research area on Low Emission Food Systems at the Alliance of Bioversity International and CIAT, and the work package “Building Policy Coherence,” explains what policy coherence means, as well as the work that his team has been doing and the next steps of the initiative, answering the following seven questions: